THE SEISMIC RUPTURE SURFACE MODEL OF THE AUGUST 17, 2024 SHIPUNSKI, KAMCHATKA, EARTHQUAKE - Konvisar, А.M.; Timoshkina, E.P.; Titkov, N.N.; Mikhailov, V.O.; Volkova, M.S.; Smirnov, V.B.; Chebrov, D.V. (Vestnik Kamčatskoj regionalʹnoj associacii "Učebno-naučnyj centr". Seriâ: Nauki o Zemle (Online), 2025)
he study presents a rupture surface model of the Shipunsky earthquake. The model consists of a single plane with a dip angle of 30°, a strike of 211°, and depths ranging from 25 to 49 km. Compared to USGS solution, the rupture surface is shifted away from the continent and extended along dip, which corresponds better to the aftershock cloud distribution according to the Kamchatka branch of the Federal Research Center «Unified Geophysical Service of RAS». The rupture exhibited nearly pure thrust, with a maximum displacement of 0.88 m and an average displacement of 0.79 m, corresponding to a seismic moment of 2.9×1019 N·m (MW = 6.9). The obtained model is in good agreement with GPS data. The model allowed for the calculation of theoretical displacement fields on the Earth’s surface in the satellite line-of-sight direction. A qualitative comparison with displacements derived from Sentinel-1A radar images was made.